Examining the patient profile and variance of management and in‐hospital outcomes for Australian adult burns patients. Issue 10 (22nd August 2022) - Tracy, Lincoln M.; Darton, Anne; Gabbe, Belinda J.; Heath, Kathryn; Kurmis, Rochelle; Lisec, Carl; Lo, Cheng; Singer, Yvonne; Wood, Fiona M.; Cleland, Heather J.
Abstract: Background: Burn injuries are a common subtype of trauma. Variation in models of care impacts clinical measures of interest, but a nation‐wide examination of these measures has not been undertaken. Using data from the Burns Registry of Australia and New Zealand (BRANZ), we explored variation between Australian adult burn services with respect to treatment and clinical measures of interest. Methods: Data for admissions July 2016 to June 2020 were extracted. Clinical measures of interest included intensive care admission, skin grafting, in‐hospital death, unplanned readmissions, and length of stay (LOS). Estimated probabilities, means, and corresponding 95% confidence intervals (CI) were calculated for each service. Results: The BRANZ recorded 8365 admissions during the study period. Variation between specialist burn services in admissions, demographics, management, and clinical measures of interest were observed. This variation remained after accounting for covariates. Specifically, the adjusted proportion (95% CI) of in‐hospital mortality ranged from 0.15% (0.10–0.21%) to 1.22% (0.9–1.5%). The adjusted mean LOS ranged from 3.8 (3.3–4.3) to 8.2 (6.7–9.7) days. Conclusions: A decade after its launch, BRANZ data displays variation between Australian specialist burn services. We suspect differences in models of care between services contributes to this variation. Ongoing research has begun to explore reasons underlying how this variation influences clinical measures of interest. Further engagement with services about models of care will enhance understanding of this variation and develop evidence‐based guidelines for burn care in Australia. Abstract : A decade after its launch, data from the Burns Registry of Australia and New Zealand displays variation between specialist burn services in Australia due to differences in models of care. Ongoing research has begun to explore reasons underlying variation in models of care influences outcomes.